The Eurasian Economic Commission’s right to appeal to the Court of Justice of the Eurasian Economic Union: Prospects for development and the European Union experience - V. V. Voynikov; T. D. Artemenko (Московский журнал международного права, 2023)
INTRODUCTION. The Eurasian Economic Union has been in existence for more than 8 years and during this time has achieved certain successes in economic integration. However, in order to continue progressive development, constant work is required to improve the institutional structure, including the reform of Eurasian Economic Commission (hereinafter referred to as the EEC), by using the experience of the European Union (hereinafter referred to as the EU). In this article explores the Eurasian Economic Commission’s right to apply to the Court of Justice of the EAEU.MATERIALS AND METHODS. This study uses the works of both Russian and foreign specialists in the field of European law and EAEU law, as well as analyses of the EU and EAEU legal acts. General scientific methods of knowledge - analysis, synthesis, induction and deduction - were used during the study. Special legal methods - formal-legal, technical-legal, the method of legal analogy, as well as the comparative legal method - were also used in the work.RESEARCH RESULTS. As follows from the analysis of the law enforcement practice of the EEC, almost every year during the monitoring of the implementation of the Union law by the member states, the Commission reveals various violations of the integration legal order, most often concerning the obligations in the field of the EAEU internal market. Based on the results of monitoring, the Commission sends notifications to member states in the form of decisions, which the member states are obliged to implement, but in the future the Commission cannot influence them if they do not implement the Commission's decision. Thus, the Eurasian Economic Commission, as a regulatory body of the Union, at this stage of development of Eurasian integration does not have enough power to perform the tasks assigned to it by the Treaty on the Eurasian Economic Union and other legal acts. In this connection, it is necessary to amend the legal acts governing the activities of the EEC, in particular to give the Commission the right to appeal to the EAEU Court on cases of non-compliance by member states with the prescriptions of the law of the Union. At the same time, it is important to note that the European Commission (hereinafter – the EC) has the relevant right, which allows it to more effectively perform the tasks assigned to it by the EU constituent treaties – this, in turn, allows the EAEU to adopt the positive features of the EC functioning, thereby improving the activities of the Eurasian Economic Commission.DISCUSSION AND CONCLUSIONS. As part of the research, the authors analyse the legal status of the EEC, its powers, the grounds for the Commission's application to the EAEU Court, the competence of the EAEU Court, as well as the prospects of the EEC's right to apply to the Court of EAEU. The authors conduct a brief comparative legal analysis of the powers of the Eurasian Economic Commission and the European Commission, as well as the competence of the European Court of Justice and the Court of EAEU. The main problem is highlighted - the lack of EEC's competence to apply to the Court of EAEU to resolve a dispute. As a result of the study, it is proposed to grant the Commission the right to apply to the Court, as well as expand the competence of the EAEU Court.